ANALISIS MANAJEMEN LAYANAN TEKNOLOGI INFORMASI DENGAN FRAMEWORK (ITIL) DOMAIN SERVICE STRATEGY - DEVA WULANDARI; Edo Arribe; Aryanto; Putriani (Department of Information System Muhammadiyah University of Riau, 2022)
Aisyiyah Pratama Clinic in Pekanbaru is one of the clinics in Pekanbaru. precisely on KH Ahmad Dahlan street. At the Pratama Aisyiyah Clinic in Pekanbaru, they already use an application in their daily lives, the application is called KANZA. The application is java-based and the application covers all work in the clinic, from the queuing system to medical records. However, this application has several drawbacks, namely the ui/ux display of the application which confuses prospective patients so that this application is less effective when used in general (by patients and clinic staff). and also this application which has been in use since 2019 has been hacked which means this application is still vulnerable to hackers. but the clinic technician quickly fixed the firewall of the KANZA application. Because of this, this research really needs to be completed to the end so that this journal can later be used as a reference for agencies experiencing cases similar to or similar to this research, and specifically at the Aisyiyah Pekanbaru Primary Clinic which is the object of our research.